PENGARUH KOMPETENSI DAN IKLIM ORGANISASI DALAM PENERAPAN APLIKASI SAP TERHADAP KEPUASAN PENGGUNA DI PT. SEMEN BATURAJA - Prayuda, Randy; Zamzam, Fakhry; Setiawan, Herri (KHOZANA: Journal of Islamic Economic and Banking, 2020)
This research particularly aims to reach The Influence of Competence and Organizational Climate in the Application of SAP Application Methods to User’s Satisfaction in Division Operation 1 and Division Operation 2 PT. Semen Baturaja (Persero), Tbk Baturaja Site. The purpose of this study specifically to obtain the results of the analysis of the influence of competence and organizational climate in the application of the System Application and Product in Data Processing (SAP) application methods to user satisfaction in Division Operation 1 and Division Operation 2 of PT Semen Baturaja (Persero) Tbk Site Baturaja, both partially or simultaneously. This research is quantitative research with explanatory methods and survey research methods. While based on the purpose of this study is to test the hypothesis with a survey and explain the causal relationship between variables, namely competence, organizational climate, and test on user satisfaction. The data analysis tool used by researchers is SmartPLS version 3.0. The results showed that competency and organizational climate simultaneously did not have a positive effect on SAP user satisfaction with an original sample value of 0.19 but the t-count value was smaller than the t-table, namely (1.30 <1.666), whereas The partial competence variable has a a positive relationship, this is evidenced by the t-count value is greater than the t-table (1.75> 1.666) and the original sample value is positive at 0.18 and the organizational climate variable also affects SAP user satisfaction in Division Operation 1 and 2 PT Semen Baturaja (Persero) with the t-count value greater than the t-table, namely (5.22> 1.666) and a positive original sample value of 0.65.